Anatomical peculiarities of leaf of wheat cultivars in the presence of cadmium in the growth medium (Experimental biology, 2015)
It was studied the anatomical structure of leaf of 5 wheat cultivars: Shagala, Kazakhstanskaya-3, Kazakhstanskaya rannaya, Melturn and Kayr under cadmium contaminated conditions (0,15 мM and 0,3 мМ CdSO4). The straight correlation between resistance of wheat cultivars by growth parameters and index of thickness epidermis of leaf wasn’t found. But it is noticed that sensitive to cadmium on growth parameters Shagala cv showed low rates of thickness of upper and lower epidermis.